1995
DOI: 10.1063/1.360423
|View full text |Cite
|
Sign up to set email alerts
|

Conduction type control from n to p type for organic pigment films purified by reactive sublimation

Abstract: The effects of purification by reactive sublimation technique and bromine doping on the Fermi level and the photovoltaic properties of n-type perylene pigment films were investigated. Photovoltage arisen from the Schottky junction between n-type perylene pigment film and Au increased significantly by repeating the train sublimation under methylamine gas atmosphere. This phenomenon was revealed to be due to the negative shift of the Fermi level resulting from the effective removal of unknown but specific impuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 17 publications
1
28
0
Order By: Relevance
“…The relevant energy levels ͑referenced to the vacuum level͒ for charge transport in PTCDI-C 13 H 27 films have been estimated to be similar to those of PTCDI-C x H 2x+1 with x =0 ͑3.4 and 5.4 eV for electrons and holes, respectively͒ 33 and are in relative agreement with energy levels predicted by quantum chemical calculations for PTCDI derivatives. 28 Gold ͑Au͒, calcium ͑Ca͒, and silver ͑Ag͒ have been previously demonstrated to provide for electron injection into PTCDI-C x H 2x+1 films and Chesterfield et al 32 reported no clear dependence of the mobility on the work function of the contact metal.…”
Section: Fabrication and Characterizationsupporting
confidence: 74%
“…The relevant energy levels ͑referenced to the vacuum level͒ for charge transport in PTCDI-C 13 H 27 films have been estimated to be similar to those of PTCDI-C x H 2x+1 with x =0 ͑3.4 and 5.4 eV for electrons and holes, respectively͒ 33 and are in relative agreement with energy levels predicted by quantum chemical calculations for PTCDI derivatives. 28 Gold ͑Au͒, calcium ͑Ca͒, and silver ͑Ag͒ have been previously demonstrated to provide for electron injection into PTCDI-C x H 2x+1 films and Chesterfield et al 32 reported no clear dependence of the mobility on the work function of the contact metal.…”
Section: Fabrication and Characterizationsupporting
confidence: 74%
“…[34] The HOMO level of T5 lies at about -5.3 eV [37] and the LUMO level at about -2.8 eV. [37] The HOMO and the LUMO levels of P13 are estimated to be ∼ -5.4 and ∼ -3.4 eV, [38] respectively.…”
Section: Introductionmentioning
confidence: 99%
“…As test materials, we adopted perylene pigment ͑Me-PTC, Fig. 1͒ as an organic film, as this has been used for organic solar cells [7][8][9] together with Au as a metal electrode.…”
mentioning
confidence: 99%